Stormwater Inlet Capacity Calculations - Bengtson, Harlan (McGraw-Hill's AccessEngineering, 2022)
This Excel workbook calculates the capacity of a curb inlet using an orifice equation for cases when the depth of stormwater flow is greater than the height of the curb opening and using a weir equation when the depth of stormwater flow is less than the height of the curb opening. The capacity of a grate inlet is calculated using an orifice equation for cases where the grate is completely submerged and using a weir equation for cases where the grate is not fully submerged.